Developments of photo‐/electro‐catalysis based on covalent organic frameworks: A review - Guiping Yang; Qing Xu; Gaofeng Zeng (Electron)
Abstract Photo‐/electro‐catalysis has the characteristics of low cost, high performance, and zero pollution, which meet the policies on environment and energy. Covalent organic frameworks (COFs), a type of crystalline organic skeleton polymers, have been widely applied and investigated in the area of photo‐/electro‐catalysis owing to their advantages of large specific surface area, regular pore size, excellent stability, flexible structural design, and massive active sites. This article reviews the structural characteristics of COFs and the strategies for strengthening the photo‐/electro‐catalytic activity of COF materials. Subsequently, deep insights were put into the photo‐/electro‐catalysis application of COF materials. In the end, the development prospects and challenges faced by COF materials in photo‐/electro‐catalysis are discussed.